Integrated petrographical and petrophysical studies of some Eocene carbonate rocks, Southwest Sinai, Egypt - Hesham Abuseda; Mohamed A. Kassab; Amir M. LaLa; Nahla A. El Sayed (Egyptian Journal of Petroleum)
The present study deals with the effect of petrographical aspects on the petrophysical properties of the Eocene rocks, which are represented by Thebes, Samalut, Darat and Tanka formations in Southwest Sinai, Egypt. The studied diagenetic factors have an important role to enhance and/or reduce the pore volume and governing the petrophysical behavior. The cementation and neomorphism are the main porosity-reducing factors, whereas dissolution and leaching out as well as the fossil content are the main porosity-enhancing factors. The petrophysical behavior of the studied facies has been outlined by measuring rock porosity, density, permeability, and electrical resistivity. The reservoir quality index (RQI) reveals that, the petrophysical features of the studied facies are consistent with the petrographical characteristics indicating bad reservoir properties for Thebes, Samalut, Darat and Tanka formations in the nearby subsurface extensions. Studying the petrophysical behavior indicates that, both permeability and formation resistivity factor are mostly dependent on the effective porosity and to some extent on the electric tortuosity.